Hyperscanning: A Valid Method to Study Neural Inter-brain Underpinnings of Social Interaction - Czeszumski, Artur; Eustergerling, Sara; Lang, Anne; Menrath, David; Gerstenberger, Michael; Schuberth, Susanne; Schreiber, Felix; Rendon, Zadkiel Zuluaga; König, Peter (Frontiers in human neuroscience, 2020)
Social interactions are a crucial part of human life. Understanding the neural underpinnings of social interactions is a challenging task that the hyperscanning method has been trying to tackle over the last two decades. Here, we review the existing literature and evaluate the current state of the hyperscanning method. We review the type of methods (fMRI, M/EEG, and fNIRS) that are used to measure brain activity from more than one participant simultaneously and weigh their pros and cons for hyperscanning. Further, we discuss different types of analyses that are used to estimate brain networks and synchronization. Lastly, we present results of hyperscanning studies in the context of different cognitive functions and their relations to social interactions. All in all, we aim to comprehensively present methods, analyses, and results from the last 20 years of hyperscanning research.